2017
DOI: 10.18632/oncotarget.18362
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed lncRNAs and miRNAs with associated ceRNA networks in aged mice with postoperative cognitive dysfunction

Abstract: Postoperative cognitive dysfunction (POCD) is a common postoperative complication observed in elderly patients. Using microarray analyses, we comprehensively compared long non-coding RNA (lncRNA), messenger RNA (mRNA), and microRNA (miRNA) expression profiles in hippocampal tissues from a mouse model of POCD and control mice. A total of 175 lncRNAs, 117 mRNAs, and 26 miRNAs were differentially expressed between POCD and control mice. Gene ontology (GO) and KEGG pathway enrichment analyses were performed to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…Previous studies have reported that several miRNAs were significantly associated with POCD [6,[18][19][20], which provide supportive evidence of the important role of miRNAs in POCD. Consistently, some of those reported miRNAs were replicated in our current study.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Previous studies have reported that several miRNAs were significantly associated with POCD [6,[18][19][20], which provide supportive evidence of the important role of miRNAs in POCD. Consistently, some of those reported miRNAs were replicated in our current study.…”
Section: Discussionsupporting
confidence: 72%
“…The miRNA expression profile data of replication cohort were downloaded from the Gene Expression Omnibus (GEO) database (Accession number: GSE95070; https:// www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE95070), which were deposited by Wei et al [19] from the Chaoyang Hospital. With regard to this dataset, hippocampus tissues of 10 mice (5 per group) were dissected, and the different miRNA expression levels between two groups were detected by Affymetrix miRNA 4.0 as well.…”
Section: Microarray and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Competing endogenous RNAs (ceRNA) network attracted more and more attention due to its significant effects on regulating the progression of cancers and nontumor diseases [10,11]. For example, HOTAIR served as a ceRNA to modulate HER2 expression via sponging miR-331-3p in GC [12].…”
Section: Introductionmentioning
confidence: 99%
“…KEGG pathway enrichment analyses revealed possible molecular pathways that might be altered in glaucoma patients. 59 However, none of these pathways is clearly known to be involved in glaucoma, and the mechanism for alleviated TM cell calcification in the ENST00000607393 knockdown cell model is unclear. Of interest, however, the mRNA expression levels of upstream components of the Wnt signaling pathway, Wnt, Frizzled, and Go/Gq, were significantly up-regulated in AH of glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%